Functional evaluation of a spiral neobladder with an angled chimney; A prospective randomized comparative study. Issue 2 (February 2023) - Moeen, Ahmed M.; Behnsawy, Hosny M.; Faragallah, Mohammad A.; Gadelkareem, Rabea A.; Osman, Mahmoud M.; Moeen, Seham M.; Hameed, Diaa A.; Zarzour, Mohamed A.
Abstract: Objectives: to assess the functional outcome of performing ureteric re-implantation to an angled short chimney in a modified spiral orthotopic ileal neobladder. Patients and methods: From January 2018 to December 2020, 90 male patients with bladder cancer underwent radical cystectomy and spiral ileal neobladder reconstruction with a chimney. Patients were randomly divided in two groups according to the position of the chimney [straight and angled] to which the ureters will be implanted. Postoperative evaluation included clinical, laboratory, radiographic and urodynamic studies. Results: There were no perioperative deaths. The mean operative time for the procedure was 4.7 ± 1.2 h in group I and 4.9 ± 1.3 h in group II (p 0.456). No intraoperative complications occurred. Early postoperative complications occurred in 8 patients. In group I, according to the modified Clavien system, GII complication occurred in 2 (5%) patients in the form of DVT in 1 (2.5%) and surgical site infection in 1 (2.5%). GIIIa occurred in 3 (7.5%) patients in the form of wound dehiscence. In group II, GII occurred in 2 (4.8%) patients in the form of prolonged urinary leakage and myocardial infarction, each occurred in one patient. GIIIb occurred in 1 (2.4%) patient in the form of intestinal leak. Poucho-ureteral reflux occurred in 10 patients [3 (7.5%) in group I and 7 (16.8%) in group II (p 0.001)]. Conclusions: The preliminary results of the right sided angled chimney during neobladder reconstruction are safe, acceptable, without an extra time to develop an anti-reflux technique and without an increased incidence of reflux.